PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI MTS AL-WASHLIYAH SIMPANG GAMBUS - Wati, Isma; Afnaria, Afnaria; Syahlan, Syahlan (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
Teachers are provided with the resources they need to incorporate project-based learning into their lesson plans through the Project Based Learning (PjBL) learning paradigm. This study is based on the observation that teachers prefer printed modules over display information because they are more visually appealing. As a result, students do not want to participate in the learning process. There are currently no opportunities for students to practice critical thinking or improve their ability to articulate mathematical ideas in this curriculum. The purpose of this study was to develop a Project Based Learning (PjBL) mathematics learning module and improve students' critical thinking skills at MTs Al-Washliyah Simpang Gambus. The paradigm used to create educational resources is called the 3-D stage of Thiagarajan Development, which stands for Define, Design, and Development. Residents of MTs Al-Washliyah Simpang Gambus became study participants. Students in class VIII A and VIII B, totaling 30 and 26 students, were used as the research sample. based on the results of the validation process carried out by six validators and producing an average score of 4.44 in the very good category. The practicality test results collected through a student response questionnaire obtained an average score of 82.7 with good criteria. With an average N-Gain of 0.71, students' critical thinking skills meet high standards for test results indicating test effectiveness.